Meningkatkan Pengetahuan Masyarakat Dalam Mengelola Penyakit Hipertensi - Baharuddin, Baharuddin; Apdiani Toalu; Andi Nurhartati (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Modern lifestyle factors cause hypertension and age, and individuals whose activity in work is low are at risk of developing hypertension from active individuals. The purpose of this service is to increase public knowledge about managing hypertension. Activity methods using counseling, poster installation, and installation of speech boards. Results with indicators of increased public knowledge about the management of hypertension prevention, the pairing of posters in predetermined places, and the installation of speech boards on the border of the hamlet. The conclusion is that there is an increase in public knowledge about hypertension and the installation of speech boards and posters in every posyandu. Conducting counseling to maintain knowledge in managing hypertension in collaboration with health workers